Earnings assimilation of post-reunification East German migrants in West Germany - Regina T. Riphahn; Irakli Sauer (LABOUR, 2024)
Abstract We investigate the wage assimilation of East Germans who migrated to West Germany after reunification (1990–99). We compare their wage assimilation to that of ethnic German immigrants from Eastern Bloc countries and international immigrants to West Germany who arrived at the same time. The analysis uses administrative as well as survey data. The results suggest that East Germans faced significant initial earnings disadvantages in West Germany, even conditional on age and education. However, these disadvantages were smaller than those of international immigrants, supporting the beneficial role of cultural similarity. The earnings gap relative to West German natives narrowed over time for all immigrants. These findings are robust to controlling for potentially endogenous return migration and labor force participation. Controls for fixed effects reveal that positive assimilation for East German and international immigrants was concentrated among highly educated immigrants.
Keywords: 330